FEASIBILITY STUDY OF ESTABLISHING AN ARTIFICIAL INSEMINATION (AI) CENTER FOR CARABAOS IN SAN ILDEFONSO, BULACAN, PHILIPPINES - Arrienda II, F.Q.; Cruz, C.V.; Perilla, M.V.; Setiawan, B.M. (Diponegoro University, 2010)
The productivity of the carabao subsector is influenced by several constraints such as social,technical, economic and policy factors. The need to enhance the local production of carabaos will helplocal farmers to increase their income. Thus, producing thorough breeds of carabaos and improving itgenetically is the best response to these constraints. This study was conducted to present the feasibilitystudy of establishing an Artificial Insemination (AI) Center and its planned area of operation in Brgy.San Juan, Ildefonso, Bulacan. The market, production, organizational and financial viability of operatingthe business would also be evaluated. This particular study will provide insights in establishing an AICenter. Included in this study is the identification of anticipated problems that could affect the businessand recommendation of specific courses of action to counteract these possible problems. Primary datawere obtained through interviews with key informants from the Philippine. Carabao Center (PCC). Togain insights about the present status of an AI Center, interviews with the technicians of PCC and privatefarm were done to get additional information. Secondary data were acquired from various literatures andfrom San Ildefonso Municipal Office. The proposed area would be 1,500 square meters that would beallotted for the laboratory and bullpen. The AI Center will operate six days a week and will be openedfrom 8 AM until 5 PM. However, customers or farmers can call the technicians beyond the office hoursin case of emergency. The total initial investment of Php 3,825,417.39 is needed in establishing the AICenter. The whole amount will be sourced from the owner’s equity. Financial projection showed an IRRof 30% with a computed NPV of Php 2,415,597.00 and a payback period of 3.97 years. Based on all themarket, technical, organizational, financial factors, projections and data analysis, it is said that thisbusiness endeavor is viable and feasible.